APPLICATION OF HYBRID GENETIC ALGORITHM TO OPTIMIZE COMPLEX PRODUCTION SCHEDULING AT PT. XYZ - Deni Yuza Mahendra (Ikatan Dosen Menulis, 2024)
PT. Carton Scheduling XYZ Problems, Delays and Losses Haunt. PT. XYZ, a carton manufacturing company, is faced with obstacles in meeting consumer demand in a timely manner. This results in losses for companies and consumers. This problem originates from a production scheduling system that is not yet optimal, namely the FCFS system which prioritizes the order of product arrival without considering the duration of work. As a result, products with short lead times have to wait a long time in queues, causing long downtime on the factory floor. The solution to overcome this problem is the use of the genetic algorithm method, a heuristic search algorithm inspired by the process of biological evolution.